Evaluating Water Levels From the Surface Water and Ocean Topography (SWOT) Mission in a Hyper‐Tidal Coastal and Estuarine Environment - I. D. Lichtman; P. S. Bell; C. Gommenginger; C. Banks; F. M. Calafat; J. Brown; S. D. P. Williams (Earth and Space Science, 2025)
Abstract The launch of the Surface Water and Ocean Topography (SWOT) satellite in December 2022 started a new era of swath altimetry, introducing an unprecedented global data set of high‐resolution two‐dimensional water level imagery. During its initial calibration and validation phase (cal/val), SWOT conducted daily observations for 3 months providing unparalleled insights into the high variability of water levels at daily and kilometer scales, far surpassing capabilities of past and current altimeters. Here, this novel data set is evaluated in the hyper‐tidal coastal‐estuarine environment of the Bristol Channel‐Severn Estuary. SWOT total water levels (TWLs) are assessed against data from a network of in‐situ water level gauges (WLGs) and compared to the performance of the CryoSat‐2 satellite altimeter. In this region, CryoSat‐2 water levels agree well with WLG data, with a Root Mean Square Difference (RMSD) of 0.17 m. Comparisons of SWOT Level 3 low rate 2 km (L3) total water level with WLG data reveal constant offsets that scale with water elevation, attributed to the spatial difference between the measurements. Once corrected, L3 TWLs achieve RMSDs ranging from 0.059 to 0.150 m against individual gauges. Overall, the scaled L3 data exhibit an RMSD of 0.137 m, a regression slope of 0.99 and offset +0.044 m, demonstrating that SWOT delivers high‐quality water level data in these dynamic and challenging environments. SWOT's altimetry images reveal complex, changing spatial patterns across the Land‐Ocean Aquatic Continuum. These daily measurements resolve fast‐changing processes, such as river discharge events, sandbank movements and storm surges — phenomena missed by the 21‐day cycle of the SWOT science phase.